Classroom Management based on the Behaviourist Theory of the students in octavo año de Educación General Básica class “F” at the Unidad Educativa Isabel de Godín in the city of Riobamba, Chimborazo province, during the academic year 2015-2016 - León Caizaguano, Carmen Lucila (2016)
The aim of this research is to emphasize the classroom management process and the behaviourist model reinforcements that influence in the English teaching learning language at eighth grade class “F” at Unidad Educativa “Isabel de Godin” in the city of Riobamba, Chimborazo Province, during the academic year 2015-2016.In order to obtain relevant information required to analyze the teaching process and the students` behavior in the English classes it was necessary to use the Ethnographic Method to describe the reality to be investigated. This research was inductive and exploratory, applied to 34 students who received the English subject within the research context. The Direct Observation technique was applied to collect information through instruments like Observation guides and Reinforcement Characterization Matrixes to have qualitative results and general conclusions. It was determined that the classroom management process was applied in a medium effectiveness level due to the constant use of reinforcement’s implementation that the teacher uses, especially when the discipline is out of control and their use is not planned. In most cases, the positive reinforcements generated a better result than the negative ones. This variable of effectiveness may be due to different factors that affect the students` academic performance such as their emotional estate, demotivation and their own characteristics (age and education level), so teachers should make a constant evaluation of their educational tools in order to have a continuous improvement and a strategic planning in their educational work